Levo-Tetrahydropalmatine Attenuates Bone Cancer Pain by Inhibiting Microglial Cells Activation - Mao-yin Zhang; Yue-peng Liu; Lian-yi Zhang; Dong-mei Yue; Dun-yi Qi; Gong-jian Liu; Su Liu (Mediators of Inflammation)
Objective. The present study is to investigate the analgesic roles of L-THP in rats with bone cancer pain caused by tumor cell implantation (TCI). Methods. Thermal hyperalgesia and mechanical allodynia were measured at different time points before and after operation. L-THP (20, 40, and 60 mg/kg) were administrated intragastrically at early phase of postoperation (before pain appearance) and later phase of postoperation (after pain appearance), respectively. The concentrations of TNF-α, IL-1β, and IL-18 in spinal cord were measured by enzyme-linked immunosorbent assay. Western blot was used to test the activation of astrocytes and microglial cells in spinal cord after TCI treatment. Results. TCI treatment induced significant thermal hyperalgesia and mechanical allodynia. Administration of L-THP at high doses significantly prevented and/or reversed bone cancer-related pain behaviors. Besides, TCI-induced activation of microglial cells and the increased levels of TNF-α and IL-18 were inhibited by L-THP administration. However, L-THP failed to affect TCI-induced astrocytes activation and IL-1β increase. Conclusion. This study suggests the possible clinical utility of L-THP in the treatment of bone cancer pain. The analgesic effects of L-THP on bone cancer pain maybe underlying the inhibition of microglial cells activation and proinflammatory cytokines increase.